(3JYdje GdeJYde aj WQjb GdJYdes - (3GdRQfhLj, HQgGf GdOjf, EHQGgje (B, (3cGf MjG b (B7s ((3jhSas)
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd Ydi Hfi BOe HGdYde hGdYed adeG QCjJ cKjQG ef WdGH GdYde ai ReGffG jLOhf Edi GdYde hdGjUdhf hef efGaYg hKeQGJg ` hgi GdYed Hg hGdfTQ ` jMQehf deG Cfge CNWChG WQjbg hJQchG TQGFWg s
(3BNQgG (B:s
... (3aUd ajeG jLdH GdQRb hajeG jefY heG jRjO ai GdYeQ heG jfbU hjbhd gPG GdKfGA cd jhe hdjdI (B: (3CfJ Gddg GdYRjR GdMcje(B, (3CfJ Gddg Gdedc GdbOhS(B, (3CfJ Gddg GdMcje GdcQje(B, (3GfJ Gddg NGdb GdNjQ hGdTQ JeJs
(3JHUQI GdeDda (B:s
(3UQM GdHZOGOj aj gOjI GdYGQajf HGSeg (B( (3EHQGgje (B) 1\13 , (3hQHeG jchf JGL GdOjf GdfYeGf Hf EHQGgje GdRQfhLj GdCYdGe (B8\35s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\ 425s
(3cTa GdXfhf (B1\ 425s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs